SPIRITUALITY AND ITS REFLECTIONS IN ONCOLOGICAL PATIENTS - Pimenta Alves, Débora; Costa Pereira, Laura; Camila Sousa Bragunce Alves; Laiza Bonela Gomes (Health and Society, 2021)
Since the dawn of mankind, science and faith have always been given as antonyms and have fought for popular recognition. However, these days the association between these areas is discussed for a better result, since believing in one of these aspects does not mean disregarding the importance of the other, even in terminal patients. The objective was to analyze the experience of spirituality/religion in supporting cancer patients and to discuss the lack of preparation and use of these tools by health professionals. The literature review was based on the BVS Brazil (Virtual Health Library), Google Scholar and PubMed databases from 2017 to 2020. The keywords used were “spirituality”, “religion”, “neoplasms” and "health". As an inclusion criterion, free full texts in English were used. The scientific search initially showed 86 articles where after the evaluation of their titles and respective abstracts, duplicates and those that were incompatible with the scope of the study were excluded, totaling 31 articles. After attaching an article separately, 31 articles were fully read for the construction of this work. Concluding that spirituality and religion are important in the lives of terminally ill patients who seek tools to cope with the disease and to continue treatment, showing the importance of these in the way of dealing with the patient, thus improving the prognosis.